Comprehensive review of the national surveys that assess E-cigarette use domains among youth and adults in the United States - Ellen Boakye; John Erhabor; Olufunmilayo Obisesan; Erfan Tasdighi; Mohammadhassan Mirbolouk; Ngozi Osuji; Albert D. Osei; Jieun Lee; Andrew P. DeFilippis; Andrew C. Stokes; Glenn A. Hirsch; Emelia J. Benjamin; et al. (Elsevier, 2023)
Summary: Surveillance of e-cigarette use among different population groups is important for the timely implementation and evaluation of tobacco regulatory policies. In this review, we identified 13 nationally representative, repeatedly conducted epidemiologic surveys that assess e-cigarette use among U.S. youth and/or adults and have been instrumental in e-cigarette surveillance. These surveys included National Youth Tobacco Survey, Youth Risk Behavior Surveillance System, Monitoring the Future Survey, International Tobacco Control Policy Evaluation Project (ITC) Youth Tobacco and Vaping Survey, Behavioral Risk Factor Surveillance System, National Health Interview Survey, Tobacco Use Supplement of the Current Population Survey, Health Information National Trends Survey, Tobacco Products and Risk Perception Surveys, ITC Four Country Smoking and Vaping Survey, National Health and Nutrition Examination Survey, National Survey on Drug Use and Health, and Population Assessment of Tobacco and Health. These surveys vary in scope and detail, with their unique strengths and the regulatory questions that can be answered using each survey data. We also highlighted the gaps in these surveys and made recommendations for improvement.